Audit Fee and Audit Quality: An Empirical Analysis in Family Firms - Homayoon, Saeid; Hakimzadeh, Maryam (International Journal of Economics and Financial Issues, 2017)
The purpose of this research is to investigate the relationship between audit fee and audit quality in family firms on the Tehran Stock Exchange. The study period is from 2007 to 2014. The sample consists of 30 family firms and 30 non-family firms. To test our hypotheses, the following methods were used: two-independent-samples t-test mean comparison and regression model. The results of this research show that there is a significant difference between audit fee in family and non-family firms, and that also family and non-family firms do not significantly differ in terms of size and auditor expertise. The results show that family firms pay lower audit fees compared to non-family firms, such that with increased family ownership, the audit fee decreases. Keywords: family firms, audit fee, audit firm size, quality, audit firm expertise JEL Classification: M4